An Evaluation of Norspermidine on Anti-fungal Effect on Mature Candida albicans Biofilms and Angiogenesis Potential of Dental Pulp Stem Cells - He, Yan; Cao, Yanfan; Xiang, Yangfan; Hu, Fengting; Tang, Fengyu; Zhang, Yanni; Albashari, Abdullkhaleg Ali; Xing, Zhenjie; Luo, Lihua; Sun, Yan; Huang, Qiang; Ye, Qingsong; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
Norspermidine (Nspd) is a kind of polyamine molecule, which is common in eukaryotes and prokaryotes. It has been reported as a potential anti-biofilms agent of bacteria, but its anti-fungal effect remains unclear. Candida albicans (C. albicans) is a common opportunistic pathogen in oral cavity of human beings. C. albicans biofilm is often seen in dental caries. In this work, we aimed to study the effect of Nspd on mature Candida albicans biofilms and to investigate how Nspd would influence human dental pulp stem cells (DPSCs). Our biofilm assays indicated that 111.7 and 55.9 mM Nspd dispersed 48 h mature fungal biofilms and showed significant fungicidal effect. 27.9 and 14.0 mM Nspd showed moderate fungicidal effect. Live/dead staining echoed the fungicidal effect. 111.7–14.0 mM Nspd showed a dose- inhibitory effect on mature fungal biofilm, where 14.0 mM Nspd reduced the metabolic activity by half compared with blank control. Moreover, we demonstrated that 111.7–27.9 mM Nspd restrained the production of hyphae form of C. albicans via SEM. Low dose Nspd (27.9 and 14.0 mM) could significantly reduce virulence related gene expression in C. albicans biofilms. MTT assay displayed a dose effect relation between 2.5–0.08 mM Nspd and DPSCs viability, where 0.63 mM Nspd reduced the viable level of DPSCs to 75% compared with blank control. Live/dead staining of DPSCs did not show distinctive difference between 0.63 mM Nspd and blank control. Vascular differentiation assay showed capillary-like structure of inducted DPSCs culture with and without 0.63 mM Nspd suggesting that it did not significantly affect angiogenic differentiation of DPSCs. Nspd can penetrate remaining dentin at low level, which is confirmed by an in vitro caries model. In conclusion, our study indicated high dosage Nspd (111.7 and 55.9 mM) could effectively disrupt and kill mature fungal biofilms. Low dosage (27.9 and 14.0 mM) showed mild anti-fungal effect on mature C. albicans biofilms. Human DPSCs were tolerate to 0.08–0.63 mM Nspd, where viability was over 75%. 0.63 mM Nspd did not affect the proliferation and angiogenetic differentiation of DPSCs.